How Can Progress Toward Ending the Human Immunodeficiency Virus Epidemic in the United States Be Monitored?. (26th November 2021) - Mitchell, Kate M; Maheu-Giroux, Mathieu; Dimitrov, Dobromir; Moore, Mia; Hughes, James P; Donnell, Deborah; Beyrer, Chris; El-Sadr, Wafaa M; Cohen, Myron S; Boily, Marie Claude
Abstract: The plan for Ending the HIV (human immunodeficiency virus) Epidemic (EHE) in the United States aims to reduce new infections by 75% by 2025 and by 90% by 2030. For EHE to be successful, it is important to accurately measure changes in numbers of new HIV infections after 5 and 10 years (to determine whether the EHE goals have been achieved) but also over shorter timescales (to monitor progress and intensify prevention efforts if required). In this viewpoint, we aim to demonstrate why the method used to monitor progress toward the EHE goals must be carefully considered. We briefly describe and discuss different methods to estimate numbers of new HIV infections based on longitudinal cohort studies, cross-sectional incidence surveys, and routine surveillance data. We particularly focus on identifying conditions under which unadjusted and adjusted estimates based on routine surveillance data can be used to estimate changes in new HIV infections. Abstract : Methods for evaluating reductions in new human immunodeficiency virus infections have different drawbacks. Representative longitudinal cohorts or cross-sectional incidence surveys can be logistically challenging. Surveillance-based measures may be heavily biased short-term by changing testing rates and subject to reporting delays.